ENTREPRENEUR INTENTION IN THE PERSPECTIVE OF PLANNED BEHAVIOR THEORY - Khairul Ikhwan; Axel Giovanni; Dian Marlina Verawati (Sosiohumaniora, 2022)
Entrepreneurship becomes a relevant topic for developing countries such as Indonesia in general and specifically for Tidar University as higher education institution that try to produce new entrepreneurs. Entrepreneurship gets individual attention from Tidar University because Tidar University has main goals to be the best in entrepreneurship. This research aims to determine the influence of attitude, subjective norm, and perceived behavioral control on the entrepreneurial intention from the student of department management at Tidar University.The population of this study was118 students of the department of management of Tidar University.Respondents in this study were selected usingsimple random sampling. This research use multiple linear regression method by using SPSS. Research results shows that attitude, subjective norm and perceived behavioral control has simultaneous effect on entrepreneurial intention. Attitude and perceived behavioral control have partially positive and significant effects on entrepreneurial intention but subjective norm did not have any effect on entrepreneurial intention. Implication from this research can be used by Tidar University to develop attitude and behavioral control to student by doing entrepreneurial training based on soft entrepreneurial skills and hard skills enhancement.